Effects of metformin and silodosin as supplementary treatments to abiraterone on human telomerase reverse transcriptase (hTERT) level in metastatic castration-resistant prostate cancer (mCRPC) cells: An in vitro study - Hidayatulla, Furqan; Andhika, Dimas P.; Prasetyawan, Widiyanto; Rahman, Zakaria A.; Pratama, Putu KD.; Hakim, Lukman (Narra Sains Indonesia, 2024)
The antiproliferative properties of metformin and silodosin have been observed in prostate cancer. Furthermore, it is hypothesized that the molecular pathways related to these drugs may impact the levels of human telomerase reverse transcriptase (hTERT) in prostate cancer cells. The aim of this study was to assess the effect of metformin and silodosin on the levels of hTERT in metastatic castration-resistant prostate cancer (mCRPC) cells. The present study employed an experimental design with a post-test-only control group. This study utilized the PC3 cell line as a model for mCRPC. A viability experiment was conducted using the CCK-8 method to determine the inhibitory concentration (IC50) values of metformin, silodosin, and abiraterone acetate (AA) after a 72-hour incubation period of PC3 cells. In order to investigate the levels of hTERT, PC3 cells were divided into two control groups: a negative control and a standard therapy with AA. Additionally, three experimental combination groups were added: metformin with AA; silodosin with AA; and metformin, silodosin and AA. The level of hTERT was measured using sandwich ELISA technique. The difference in hTERT levels was assessed using ANOVA followed by a post hoc test. The IC50 values for metformin, silodosin, and AA were 17.7 mM, 44.162 mM, and 66.9 μM, respectively. Our data indicated that the combination of metformin with AA and the combination of metformin, silodosin and AA decreased the hTERT levels when compared to control, AA, and silodosin with AA. The administration of metformin resulted in a reduction of hTERT levels in the PC3 cell line, but the impact of silodosin on hTERT levels was not statistically significant compared to AA group.